2011
DOI: 10.1144/sp357.2
|View full text |Cite
|
Sign up to set email alerts
|

New Palaeoproterozoic palaeomagnetic data from the Kaapvaal Craton, South Africa

Abstract: Palaeomagnetic data from the well-dated 2060.6±0.5 Ma Phalaborwa Complex in South Africa (Kaapvaal Craton) are of excellent quality. High unblocking components are carried by magnetite and single polarity remanence directions (mean declination 5.0°, inclination 57.3°, α95 = 5.2°) yield a palaeomagnetic pole (latitude 27.7°N, longitude 35.8°E, A95 = 6.6°) that overlaps with existing poles from the near coeval 2054.4±1.3 Ma Bushveld Complex. The Phalaborwa and Bushveld complex poles, along with poles from the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…1). Paleoproterozoic magnetizations that pass reversal and baked-contact tests were reported for the BHDS (Letts et al, 2005(Letts et al, , 2011Lubnina et al, 2010) and are confirmed by combined U-Pb geochronology, geochemistry, and paleomagnetic data sets (Olsson et al, 2016;Wabo et al, 2019). Baddeleyite U-Pb crystallization ages of 12 dikes range between ca.…”
Section: The Black Hills Dike Swarmsupporting
confidence: 57%
“…1). Paleoproterozoic magnetizations that pass reversal and baked-contact tests were reported for the BHDS (Letts et al, 2005(Letts et al, , 2011Lubnina et al, 2010) and are confirmed by combined U-Pb geochronology, geochemistry, and paleomagnetic data sets (Olsson et al, 2016;Wabo et al, 2019). Baddeleyite U-Pb crystallization ages of 12 dikes range between ca.…”
Section: The Black Hills Dike Swarmsupporting
confidence: 57%
“…Goutham et al 2006;Pradhan et al 2008;Letts et al 2010;Pisarevsky et al 2013) to argue for the primary nature of magnetization in the absence of field tests, although remagnetization can also produce dual polarity results (e.g Evans et al 2002;De Kock et al 2015;. …”
mentioning
confidence: 99%
“…The chief mineral produced is copper, which is found in the copper-bearing rocks such as carbonatite and foskorite (Southwood and Cairncross, 2017). Copper-and magnetite-bearing rocks are all enclosed in the Palabora Igneous Complex, which is complex in formation with dimensions extending 6.5 km by 2.5 km (Southwood and Cairncross 2017;Letts et al, 2011).…”
Section: Background Of the Study Areamentioning
confidence: 99%